2008
DOI: 10.1158/0008-5472.can-08-2514
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclin D1 as a Mediator of c-Met– and β-Catenin–Induced Hepatocarcinogenesis

Abstract: Activation of c-Met signaling and B-catenin mutations are frequent genetic events observed in liver cancer development. Recently, we demonstrated that activated B-catenin can cooperate with c-Met to induce liver cancer formation in a mouse model. Cyclin D1 (CCND1) is an important cell cycle regulator that is considered to be a downstream target of B-catenin. To determine the importance of CCND1 as a mediator of c-Met-and B-catenin-induced hepatocarcinogenesis, we investigated the genetic interactions between C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 44 publications
0
72
1
1
Order By: Relevance
“…Co‐activation of MET and β‐catenin often occurs in HCC 22. Codelivery of both MET and CAT (ΔN90‐β‐catenin, exon 3 deleted), but neither MET nor CAT alone, into mouse livers using the sleeping beauty transposon system efficiently induces HCC within several weeks 22, 23, 24. Therefore, this model (referred to here as MET/CAT) is useful for studying the functions of genes in hepatocarcinogenesis because of its clinical relevance and efficiency of HCC induction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co‐activation of MET and β‐catenin often occurs in HCC 22. Codelivery of both MET and CAT (ΔN90‐β‐catenin, exon 3 deleted), but neither MET nor CAT alone, into mouse livers using the sleeping beauty transposon system efficiently induces HCC within several weeks 22, 23, 24. Therefore, this model (referred to here as MET/CAT) is useful for studying the functions of genes in hepatocarcinogenesis because of its clinical relevance and efficiency of HCC induction.…”
Section: Resultsmentioning
confidence: 99%
“…For the c‐met (MET)/constitutively active β‐catenin (CAT)‐driven HCC model,19, 22, 23, 24 55 μg of total plasmids, encoding the sleeping beauty transposase (HSB2) and transposons with oncogenes MET/CAT and gaussia luciferase (Gluc) (22.5 μg pT3‐EF1a‐c‐MET [human], 22.5 μg pT3‐EF1a‐DN90‐β‐catenin [human], 5 μg pT3‐Gluc1, and 5 μg HSB2) were injected hydrodynamically into age‐ and sex‐matched mice. Six weeks after MET/CAT injection, mice were treated with vehicle (30% captisol), ceritinib (25 mg/kg), sorafenib (25 mg/kg), or a combination of ceritinib and sorafenib by oral gavage daily for 4 weeks prior to being sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of c-Met signaling and β-catenin mutations are frequent genetic occurrences observed in liver cancer initiation (9)(10)(11). Previous studies have reported that c-Met and β-catenin are coactivated in HCC, and possess a possible correlation with hepatic carcinogenesis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Following the review of previous studies on FAK, c-Met and β-catenin oncoproteins, their correlation with HCC has been identified in a variety of studies (12,13,(18)(19)(20)(21)(22). However, the intercorrelation among them requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Each step in the development of HCC appears to be linked to separate genetic and epigenetic aberrations. These changes are associated with alterations in the expression or formation of an oncogene or a tumor suppressor gene (Patil et al, 2009). In addition, several previous studies have also reported associations between genetic polymorphisms and the risk of HCC and/or HBV clearance, e.g., histone deacetylase-10 (HDAC10 ) and secreted phosphoprotein-1 (SPP1) polymorphisms, and interleukin-10 (IL10) haplotypes were also shown to be associated with HBV clearance and/or HCC development (Lin et al, 2005;Park et al, 2007;Shin et al, 2003;Shin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%